The optimization of acid hydrolysis on bioethanol production from durian peel waste (Durio zibethinus murr) - Shanta Noventhya Ginting; Epi Kristina Simanullang; Lindu Parningotan Simanullang; Bajoka Nainggolan; Saronom Silaban (Jurnal Pendidikan Kimia (JPKim), 2018)
Abstract:       The dependence on fossil fuels is a big problem and needs an urgent solution. One of the steps taken is the utilization of bioethanol "lignocellulose". This research uses natural material with high lignocellulose content that is durian peel waste and aims to make durian peel waste as raw material of bioethanol production with variation of H2SO4 concentration, temperature, and acid hydrolysis time. The variable used is H2SO4 concentration of 1%, 3%, and 5%; temperature of 100˚C, 120˚C, and 140˚C; and time of 120 minutes, 150 minutes, and 180 minutes. From the analysis, the highest bioethanol purity was obtained at 99.81% at 100˚C and hydrolysis time at 120 minutes.Keywords:acid hydrolysis; bioethanol; durian peel waste; optimization